2021
DOI: 10.1016/j.bioactmat.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mimicking 3D bioglass-nanoclay scaffolds promote endogenous bone regeneration

Abstract: Large bone defect repair requires biomaterials that promote angiogenesis and osteogenesis. In present work, a nanoclay (Laponite, XLS)-functionalized 3D bioglass (BG) scaffold with hypoxia mimicking property was prepared by foam replication coupled with UV photopolymerization methods. Our data revealed that the incorporation of XLS can significantly promote the mechanical property of the scaffold and the osteogenic differentiation of human adipose mesenchymal stem cells (ADSCs) compared to the properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 44 publications
(35 reference statements)
1
31
1
Order By: Relevance
“…Therefore, it is reasonable to presume that the PCL/LAP scaffold stimulated extracellular matrix mineralization by accelerating Col-1α1 synthesis to provide a matrix for osteoid formation, which might be attributed to the increased RUNX2 level induced by LAP released from PCL/LAP. Similar trends were observed in previous studies of LAP-containing biomaterials [ 21 , 22 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is reasonable to presume that the PCL/LAP scaffold stimulated extracellular matrix mineralization by accelerating Col-1α1 synthesis to provide a matrix for osteoid formation, which might be attributed to the increased RUNX2 level induced by LAP released from PCL/LAP. Similar trends were observed in previous studies of LAP-containing biomaterials [ 21 , 22 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…The degradation products of LAP consist of silicon [Si(OH) 4 ], magnesium (Mg 2+ ) and lithium (Li + ) ions [ 37 , 48 ]. All these degradation products have been regarded as playing considerable roles in osteogenesis and angiogenesis [ 16 , 37 , 40 ]. These results confirm the osteoconductive and osteoinductive properties of LAP-incorporated PCL in vivo and suggest that LAP-incorporated PCL can be envisioned as a promising candidate for vascularized bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that HX enhances vascular endothelial growth factor ( VEGF ) and interleukin 6 ( IL6 ) expression as well as it coordinates stem cells homing and mobilization [ 64 ]. Along the line, using biomaterials scaffold incorporated with HX inducing agents (Desferoxamine) to enhance OD of adipose tissue-derived mesenchymal stem cells reported the efficiency of scaffolds to upregulate HIF1α and VEGF expression and to improve OD in humans [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytocompatibility and bioactivity of these matrices were further improved by changing nano-micro structures, anisotropic topography, degradation behavior and mechanical performance [ [16] , [17] , [18] , [19] ]. Various polymers, mineral nanomaterials, and biomacromolecules were also introduced into silk-based bone matrices, endowing them with angiogenesis and osteogenesis inducing and control features [ 5 , 20 , 21 ]. However, a gap maintains for SF matrices to further improve the angiogenic and osteogenic capacity in a dynamic fashion for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%